2022
DOI: 10.1155/2022/1359243
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Artificial Intelligence and Virtual Reality in Martial Arts Sports on Students’ Physical and Mental Health

Abstract: As a treasure left over from Chinese traditional culture, martial arts have a long history and lasts for a long time. With the country’s promotion and support of martial arts culture, martial arts have also attracted more and more people’s attention. In order to carry forward the martial arts culture, the combination of martial arts and sports has formed a set of martial arts sports suitable for today’s students, such as martial arts aerobics. It is used as a class exercise for students, and basically, every s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Research is needed to determine the precise effects of artificial intelligence and virtual reality on the physical and mental growth of pupils participating in martial arts athletics. Wang et al (Li et al 2022 ) have shown that artificial intelligence and virtual reality martial arts can boost boys’ and girls’ lung capacities by about 14% and 16%, respectively. It also demonstrates that the effects on bodily conditioning can raise boys’ and girls’ lower-body power by 3% and adaptability by 30%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Research is needed to determine the precise effects of artificial intelligence and virtual reality on the physical and mental growth of pupils participating in martial arts athletics. Wang et al (Li et al 2022 ) have shown that artificial intelligence and virtual reality martial arts can boost boys’ and girls’ lung capacities by about 14% and 16%, respectively. It also demonstrates that the effects on bodily conditioning can raise boys’ and girls’ lower-body power by 3% and adaptability by 30%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%